Explanations of, and responses to, youth homelessness in local authority housing departments - Harding, Jamie (1999)
This article examines the relationship between beliefs about youth homelessness and the steps being taken by local authorities to tackle the problem, based on interviews with officers responsible for dealing with youth homelessness in north-eastern local authorities. Officers blamed young people's homelessness on a wide range of factors, but the action they thought appropriate to tackle the problem tended to focus on making more accommodation available or supporting young people to live in it. Officers expressed frustration at their inability to provide adequate support. It appeared that action to meet young people's needs was most likely to be taken when it also incorporated a `housing management' objective such as filling empty properties. - Reproduced
Keywords: Homeless; Local government; Youth; Housing